2019
DOI: 10.1108/rpj-06-2018-0149
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and water absorption behaviour of PLA and PLA/wood composites prepared by 3D printing and injection moulding

Abstract: Purpose This papers aims to study the influence of water absorption on the mechanical properties of poly lactic acid (PLA) and PLA/Wood composites. Virgin PLA and PLA/Wood double-bone-shaped specimens were prepared by two methods: injection moulding and 3D printing. The results were compared to each other and showed the influence of the production method on the properties of the produced parts. Design/methodology/approach Morphology studies were done by scanning electron microscopy (SEM) from fracture surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…This is due to water being absorbed by the material, which means that water molecules disperse between polymer chains, and reduce chain-chain interaction. It was reported that PLA might absorb up to~1% water by weight [44]. The largest deformation difference occurs for the reference sample, which indicates the highest water absorption.…”
Section: Flexural and Tensile Strength Testsmentioning
confidence: 98%
“…This is due to water being absorbed by the material, which means that water molecules disperse between polymer chains, and reduce chain-chain interaction. It was reported that PLA might absorb up to~1% water by weight [44]. The largest deformation difference occurs for the reference sample, which indicates the highest water absorption.…”
Section: Flexural and Tensile Strength Testsmentioning
confidence: 98%
“…However, the barrier properties of PLA, with limited moisture uptake, limit functionality of the responsive photonic dopant. [ 38 ]…”
Section: Resultsmentioning
confidence: 99%
“…We have not seen many reports on the transient hardening of PLA. PLA and PLA/wood composites prepared by injection molding and 3D printing have been evaluated for their mechanical properties [47]. Studies have also been done to determine how the water absorption characteristics of polymer materials affect the base resins of dentures [48,49].…”
Section: Temporary Strength Increase Brought About By Immersionmentioning
confidence: 99%